Research on mobile intelligent mine platform based on risk control. Issue 1 (November 2020) - Wu, Chao; Wu, Yuliang; Zhu, Changsheng; Zhang, Chengyuan; Song, Qingjun
Abstract: It is a challenge to effectively solve the "bottleneck problem" of the information management and safety evaluation of coal mine. In case of unexpected events, it is hard for miners to rapidly know the status of environment and find solutions. On the basis of the concept of mobile work, we design a mobile intelligent mining platform aiming for an early warning. That platform is a comprehensive application of the Internet of Things, mobile Internet, intelligent control theory and other technologies. It is mainly composed of four parts: underground sensor, underground subsystem, mobile intelligent mine platform and mobile terminal. An early warning combination model is proposed and described to address this issue. The fuzzy AHP is combined with neural network because of fault-tolerant ability, parallel processing ability, processing non-linear problem ability. The paper adopts the neural network model and the fuzzy AHP model to construct a coal mine safety early warning model. With modern wireless 4G network and geographic information technology, mobile terminal allows staff to know not only the specific risk level but also the status of the scene nearby. The intelligent terminal user interface provides real-time queries and handles processes coal mine production, safety and management. It achieves comprehensive monitoring and integration management both on the automation system and security system.